SYMPATHO-ADRENAL SYSTEM DYSFUNCTION AND LIPID PEROXIDATION IN MEN WITH TYPE 2 DIABETES MELLITUS AND ARTERIAL HYPERTENSION - Sh. K. Yusupova (Российский кардиологический журнал)
The study evaluated sympatho-adrenal system (SAS) function and lipid peroxidation (LPO) in 105 men: 95 patients with Type 2 diabetes mellitus (DM-2), including 50 individuals with arterial hypertension (AH), and 15 healthy controls. The measurements included 24-hour urine excretion of adrenaline, noradrenalin, dopamine, and DOPA, serum levels of an LPO product, malonic dialdehyde (MDA), and lipid profile (total cholesterol, low and high-density lipoprotein cholesterol, triglycerides). In DM-2 patients with AH, catecholamine and DOPA excretion, as well as serum MDA levels, were significantly higher than in controls or DM-2 patients without AH. Therefore, SAS activation, LPO, and insulin deficiency could increase metabolic disturbances in DM-2 and AH patients, which affects clinical course severity and disease prognosis.